Spontaneous Recession Repair after Orthodontic Treatment: Case Report with the Use of Digital Approach for Quantification of Soft Tissue Changes - Myroslav Goncharuk-Khomyn; Oleksandr Krasnokutskyy; Mykola Boichuk; Vitaliy Rusyn; Marharyta Hliudzyk-Shemota (Hindawi Limited, 2023)
The article presents a case of spontaneous recession repair in a male patient with Class II malocclusion, division 1, after orthodontic treatment with aligners. The difference in digital recession depth was measured before and at the end of treatment by means of automatic intraoral scans superimposition within adapted software while using "Cross section" and "Measuring" instruments. Digital analysis of intraoral scans obtained before and at the end of treatment has revealed that recessions within the area of teeth 1.5, 1.4, 1.3, 1.2, 1.1, 2.1, 2.2, 2.3, 2.4, and 2.5 have improved, and recession depth reduced by 0.73±0.08 mm, 1.02±0.09 mm, 1.86±0.13 mm, 0.72±0.09 mm, 0.73±0.04 mm, 0.67±0.06 mm, 0.66±0.07 mm, 1.50±0.12 mm, 1.10±0.05 mm, and 0.45±0.04 mm, appropriately. The present case report emphasizes that orthodontic correction of altered tooth position (angulation, inclination, and rotation) under certain clinical conditions may be considered as an effective method for soft tissue contour optimization in cases when pre-treatment tooth position could be interpreted as a causative factor or associated with diagnosed recession. The following outcomes could be related, but not limited to creeping attachment mechanism, bone-housing centering effects, optimization of occlusal load distribution with ruling out peak zones of strain accumulation, and mucogingival stress leveling. Due to the authors' knowledge, the present case report is the first one where the signs of spontaneous recession repair after orthodontic treatment were evidenced with the intraoral scans and quantified by the specifically implemented digital analysis approach.